Profil Efikasi Diri Karir Pengurus Forum Komunikasi Siswa Kota Bandung - Jaya, Nur Nabila; Ramadhani, Rina Nurhudi; Yusuf, Syamsu (JURNAL KONSELING GUSJIGANG, 2024)
Every period in life has its difficulties, and adolescence is no different. Confusion in determining the future, for example. But not infrequently, some of them actually feel challenged and are looking forward to the moment at that time. Therefore, this study tries to find out the career self-efficacy that is useful in dealing with uncertainty in planning their careers. The subjects in this study were the administrators of the Forum Komunikasi Kota Bandung term of office as many as 75 respondents. This study uses a quantitative research design, namely a cross sectional survey design by collecting data from a sample at one point in time. Overall, the results of this study indicate that the Bandung City Student Communication Forum administrators are mostly in the moderate category for almost all aspects of career efficacy, both cognitive and affective.